Factors influencing the Ethics and Anti-Corruption Commission in the fight against corruption in Kenya - Aluda, M. C. (Strathmore University, 2025)
This study examined the factors influencing Kenya's Ethics and Anti-Corruption Commission (EACC) in its efforts to combat corruption. Despite the establishment of the EACC in 2011 and subsequent anti-corruption initiatives, Kenya continues to grapple with widespread corruption across both public and private sectors attributable to various factors. The main objective of the study was to determine the factors influencing the EACC in executing its mandate. Specifically, the study sought to: identify legal and institutional framework factors hindering EACC's effectiveness; evaluate the extent of political interference in EACC operations; analyze how resource allocation affects the commission's anti-corruption efforts; and identify coordination challenges in inter-agency cooperation. The study was grounded in Institutional Theory by Selznick (1949), employing a descriptive research design with convergent parallel mixed-methods approach. Data collection involved document analysis, questionnaires administered to 103 EACC officials, and interviews with five key anti-corruption experts. Quantitative data was analyzed using descriptive statistics and presented through frequency tables, means, standard deviations, and percentages. Qualitative data underwent thematic analysis using NVivo software with results presented as verbatim quotes. Key findings revealed significant operational constraints including limited technological, financial, and human resources. Institutional barriers, particularly political interference and weak interagency coordination, substantially impeded EACC effectiveness. Weak rule of law emerged as the primary weakness in Kenya's anti-corruption framework, while limited technology utilization resulted from inadequate budgetary allocation. Based on these findings, the study recommends strengthening EACC's institutional independence, enhancing resource allocation, improving inter-agency coordination mechanisms, and reinforcing legal frameworks. These insights contribute to both theoretical understanding of anti-corruption agency effectiveness in developing countries and provide practical recommendations for policy reform in Kenya and similar contexts in Sub-Saharan Africa.
Full - text thesis